Using near-infrared spectroscopy to investigate the amylose content in rice - Rahim, H. A. (2013)
Nowadays, there are many breeding program to improve the quality of rice since the direct measurement (iodine colorimetric) is time consuming, complex and environmentally unfriendly. The objective of this study was to analyze the amylose content (AC) in several types of local rice and import rice in Malaysia. Next is to investigate suitable rice intake for diabetic patient. In this study, non-destructive method by using Near-Infrared Spectroscopy (NIRS) was used to measure the amylose content of single rice grain for milled rice and brown rice. The result showed that the AC for the brown rice was higher than basmati rice followed by local white rice. Therefore, the high amylose content is most suitable for the diabetic patient. Thus, NIRS was a convenient way to screen the quality of rice as well as increase the global competitive for farmers in agriculture field.